Precise nucleosome positioning in the promoter of the chicken beta A globin gene. - Kefalas, P (1988)
Histone octamers were reconstituted onto 5' end-labelled DNA fragments derived from the promoter region of the chicken beta A globin gene. The location of the reconstituted histone octamer with respect to the DNA sequence of each fragment was assessed by Exonuclease III digestion of purified nucleosome monomers. By this approach we have found a strong preference for histone octamers to be positioned over nucleotides -206 to -62 relative to the gene cap site. This stretch of DNA contains all those 5' beta globin sequences which, by DNase footprinting, bind specific protein factors and incorporates three promoter consensus sequence motifs. The upstream terminal 32 base pairs of this DNA segment contains the binding sites for the erythrocyte specific G-string binding protein and transcription factor Spl and appears to be relatively weakly bound to the histone octamer.